On the issue of legal regulation of food labeling in the ensuring food safety context - Saskevich, Veranika V. (Journal of the Belarusian State University. Law, 2026)
This article analyses the legal aspects of food labeling as a means of ensuring their safety and quality, as well as a factor in raising public awareness of food security. Attention is paid to shortcomings in the regulation of the state information system for labeling goods with unified control marks or identification tools. The author proposes ways to improve legislation to more fully ensure everyone’s right to information and protect consumer rights. She also substantiates legal measures aimed at expanding the potential of food labeling to promote organic products and healthy eating habits in Belarus.
Keywords: food labeling; food safety; right to adequate food; right to information; consumer protection